Grammar Deviation in the pronunciation of the Arab tribes - Ashour, Ahmed; Hamid, Noor AbdulBasset (Al-Adab Journal, 2021)
Grammatical changes in dialects are few when compared to other changes in linguistic, vocal, grammatical, and semantic levels, some tribes have contradicted some of the characteristics of the common language in their pronunciation. Therefore, we found changes related to certain exposed analogues verbs, such parsıng the verb, to neglect a work that was the doer, or to derive some names that were prevented from derivation, to change the intransitive verbs into transative, or to express what was based on changes related to some non-changes, such as the frequency of words between parsing and construction contexts, including what differed between individuality, Deuteronomy and plural. Therefore, The aim of the study was to monitor these grammatical changes in the books of modernists, by following the curriculum of evolutionary history. However, it sometimes influenced the Qur’anic use, and we found some verses that came in accordance with the pronunciation of these tribes, and the differences they made, which sometimes affected the uses of neighboring tribes.